The Parasitic Wasp, Cotesia congregata (Say), Consists of Two Incipient Species Isolated by Asymmetric Reproductive Incompatibility and Hybrid Inability to Overcome Host Defenses - Bredlau, Justin P.; Kuhar, Daniel; Gundersen-Rindal, Dawn E.; Kester, Karen M. (Frontiers in Ecology and Evolution, 2019)
Parasitic wasps are highly diverse and play a major role in suppression of herbivorous insect pest populations. Several previously identified species of parasitic wasps have been found to be complexes of cryptic species resulting from adaptations to specific hosts or host foodplants. Cotesia congregata (Say) (Hymenoptera: Braconidae), which has long served as a model system for host-parasitoid interactions, can be used for investigating the process of diversification among sympatric populations that differ in host and host foodplant usage. Two incipient species of C. congregata have been identified in the USA mid-Atlantic region, “MsT wasps” originate from Manduca sexta (L.) (Lepidoptera: Sphingidae) on tobacco and “CcC wasps” originate from Ceratomia catalpae (Boisduval) (Lepidoptera: Sphingidae) on catalpa. Both wasp sources can develop in either host species. Hybrids resulting from MsT♂xCcC♀ crosses are fertile, whereas hybrids from CcC♂xMsT♀ crosses are typically sterile. In this study, we compared relative expression in vivo of seven C. congregata bracovirus (CcBV) genes among MsT and CcC parental and hybrid crosses. Also, we established hybrid crosses between MsT and CcC wasps and four additional host foodplant sources of C. congregata. Patterns of relative expression in vivo of MsT and CcC CcBV genes differed; a few were not expressed in hosts parasitized by CcC wasps. Overall, relative expression of CcBV genes from MsT and CcC wasps did not differ with respect to the host species parasitized. Low or absent expression of CcBV genes was found in hosts parasitized by sterile hybrids. For the most part, the other four host-foodplant wasp sources were reproductively compatible with either MsT or CcC wasps and hybrid crosses with the alternative wasp source were asymmetrically sterile. Crosses involving CcC males or MsT females produced sterile hybrids that lacked mature ovaries. Cumulatively, results indicate that C. congregata is composed of two sympatric incipient species that can utilize multiple host species rather than several host-associated races or cryptic species.